THE RELATION BETWEEN SERVICE QUALITY AND SATISFACTION OF CLASS 1 INPATIENTS AT GRANDMED LUBUK PAKAM HOSPITAL - Luci Riani Br Ginting; Adelia Kristy Br Ginting (JURNAL KESMAS DAN GIZI (JKG), 2022)
Service quality is a measure of how well the level of service provided is able to meet customer (patient) expectations. Service quality consists of real, reliability, responsiveness, assurance, empathy. Patient satisfaction is a measure of the success of health service performance, this can be seen from the suitability of expectations and reality received by patients in service. This study aims to determine the relation between service quality and satisfaction of class 1 inpatients at Grandmed Lubuk Pakam Hospital. This study uses an analytical survey with a cross sectional approach. The sample in this study was inpatient class 1 at the Grandmed Hospital Lubuk Pakam as many as 32 respondents with the accidental sampling method using the chi square test with a 95% confidence level = (0.05). The results showed that there was a significant relationship between service quality and satisfaction of class 1 inpatients where tangible p (0.038) <? (0.05), reliability p (0.003) <? (0.05), responsiveness p (0.026) <? (0.05), assurance p (0.002) <? (0.05) and empathy p (0.005) <? (0.05). It is expected for health workers to improve the quality of services provided, especially in class I inpatient rooms, clean the room, apply smiles, greetings, speed, can provide excellent service and punctuality in the examination schedule for patients so as to create a relationship between patients and nurses. For hospital management, it is necessary to develop an information management system to facilitate service and quick evaluation of hospital needs.